2018
DOI: 10.1103/physreva.98.053435
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal momentum of the electron at the tunneling exit

Abstract: The longitudinal momentum of the electron at the tunneling exit is a useful quantity to make sense of the tunneling ionization process. It was usually assumed to be zero from a classical argument, but recent experiments show that it must be nonzero in order to explain the measured electron momentum distributions. In this article we show that the flow momentum of the probability fluid is a sensible quantum mechanical definition for tunneling-exit momentum, and it can be (and in general is) nonzero at the tunnel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
1
12
0
2
Order By: Relevance
“…This is in line with previous works, e.g. [38], that have also shown that for a 1D model the tunneling ionization produces a non-zero outgoing momentum at the tunnel exit. Clearly, the simple-man's scenario does not apply for this specific situation as there is a pronounced delay and the arrival time exhibits a broad distribution.…”
Section: A Tunneling From a Discrete Statesupporting
confidence: 93%
“…This is in line with previous works, e.g. [38], that have also shown that for a 1D model the tunneling ionization produces a non-zero outgoing momentum at the tunnel exit. Clearly, the simple-man's scenario does not apply for this specific situation as there is a pronounced delay and the arrival time exhibits a broad distribution.…”
Section: A Tunneling From a Discrete Statesupporting
confidence: 93%
“…(See, e.g., a summary of several different criteria in [36]) What should be the velocity of the electron at the tunneling exit point? [37][38][39][40][41][42] It is found that the final electron momentum distribution depends sensitively on how these initial conditions are assigned.…”
Section: Introductionmentioning
confidence: 99%
“…The VD method has been shown to yield good agreements with TDSE calculations on photoelectron momentum distributions [43,44,48], although quantum interferences are necessarily lost due to the transformation to classical trajectories. Besides, the VD technique has been found very useful in gaining insights into the ultrafast ionization process [41,42,[49][50][51]. The goal of the current paper is to present a further development of the VD method.…”
Section: Introductionmentioning
confidence: 99%
“…it is beyond the validity range of well-known theories [31]. Recent theoretical approximations of strong-field ionization meeting such conditions often employ classical dynamics, where the choice of proper initial conditions, including the longitudinal momentum, is an important open question [18,[32][33][34][35][36][37][38][39],…”
mentioning
confidence: 99%